A comprehensive insight into the role of barium in catalytic performance of Co/Al2O3 catalyst for Fischer-Tropsch synthesis. (15th November 2019) - Guo, Shupeng; Wang, Qiang; Wang, Min; Ma, Zhongyi; Wang, Jungang; Hou, Bo; Chen, Congbiao; Xia, Ming; Jia, Litao; Li, Debao
Graphical abstract: Highlights: Ba transfered electron to cobalt surface and then affect the adsorption of H2 and CO on the catalyst surface. Ba decreased CH4 selectivity by increasing the apparent activation energy of the whole reaction. Ba suppressed the hydrogenation of olefins by enhancing the olefins desorption. Abstract: The role of Ba in Fischer-Tropsch synthesis (FTS) from syngas over Co/γ-Al2 O3 catalyst was investigated using a combined experimental and Density functional theory (DFT) method. The reducibility of catalysts was improved with the addition of Ba. Furthermore, the cobalt surface electronic density was increased by the existence of Ba on the surface of catalyst, leading to decrease surface H concentrations, promote CO adsorption and dissociation and then reduce the selectivity of CH4 and enhance the selectivity of C5 + and o/p ratio of C3 . The DFT calculation results indicate that the existence of Ba can decrease CH4 selectivity by increasing the apparent activation energy of the whole reaction, and suppress the hydrogenation of olefins by enhancing the olefins desorption and then improve the o/p ratio of C3 . These results give mechanistic insights into why the catalytic performances of Ba-modified Co-based catalysts are better than clean Co-based catalysts and could open up new avenues for the future design of highly active and selective Co-based catalysts.